Evidence on the Improvement of the Thermal Comfort Index and Habitability in Bioclimatic Spaces of the Mediterranean Region. - Guerrero Serrano, Pedro Miguel; Salvo-Tierra, Ángel Enrique (My University, 2025)
Contemporary bioclimatic design is based on the synergistic integration of five essential pillars: urban planning, architecture, vegetation, landscaping, and materials. This strategic combination enables the creation of sustainable spaces that optimize thermal comfort and habitability. Bioclimatic urban planning establishes environmental planning through the efficientarrangement of green spaces and ecological corridors, promoting air circulation and reducing the heat island effect (Cano Giraldo, 2024). Meanwhile, bioclimatic architecture incorporates construction solutions that maximize the use of solar radiation, cross ventilation, and energy efficiency (Bunimov, 2023). The use of vegetation and landscaping provides natural barriers that stabilize temperature and enhance thermal comfort, as observed in the Oasis Colectivo project, which employs strategically placed trees and gardens to reduce ambient temperature (Gamboa et al., 2024). Finally, the appropriate selection of materials, such as those with high thermal inertia or reflective properties, complements these strategies, contributing to efficient natural air conditioning (Rodríguez Escandell, 2024). The balanced combination of these elements forms the foundation of modern bioclimatic design, aimed at improving human well-being and urban sustainability.
El diseño bioclimático contemporáneo se basa en la integración sinérgica de cinco pilares esenciales: urbanismo, arquitectura, vegetación, paisajismo y materiales. Esta combinación estratégica permite crear espacios sostenibles que optimizan el confort térmico y la habitabilidad. El urbanismo bioclimático establece una planificación ambiental a través de la eficiente disposición de espacios verdes y corredores ecológicos, promoviendo la circulación del aire y reduciendo el efecto isla de calor (Cano Giraldo, 2024). Por su parte, la arquitectura bioclimática incorpora soluciones constructivas que maximizan el aprovechamiento de la radiación solar, la ventilación cruzada y la eficiencia energética (Bunimov, 2023). El uso de vegetación y paisajismo proporciona barreras naturales que estabilizan la temperatura y mejoran el confort térmico, como se observa en el proyecto Oasis Colectivo, que emplea árboles y jardines estratégicamente situados para reducir la temperatura ambiente (Gamboa et al., 2024). Por último, la adecuada selección de materiales, como aquellos con alta inercia térmica o propiedades reflectantes, complementa estas estrategias, contribuyendo a una eficiente climatización natural (Rodríguez Escandell, 2024). La combinación equilibrada de estos elementos constituye la base del diseño bioclimático moderno, orientado a mejorar el bienestar humano y la sostenibilidad urbana.
Keywords: Bioclimatología; Ecología urbana; Flora urbana; Urban ecology; Urban planning; Thermal; Bioclimatism; Vegetation